Pursuits of Unhappiness as Political Economy: Lubitsch’s Wartime Trilogy - Jukić, Tatjana (2012)
Taking up Ninotchka as the point of departure, where it is around Garbo in Ninotchka that Lubitsch organizes his position on the political, I argue that The Shop Around the Corner and To Be or Not to Be work as cinematic sessions to process the implications of this position. It is for this reason that I address the three films as trilogy. Entailed in these sessions is a peculiar political economy which, of course, bears on Marx, but is as symptomatic of the conditions of film as such. Also, this political economy demands a recourse to psychoanalysis (just as Lubitsch invokes psychoanalysis in That Uncertain Feeling, a kind of syncope in the above trilogy). This in turn provides a position from where to address the economic problem of psychoanalysis itself.
Projekt MZOS
ENG